Effectiveness of an intervention to facilitate prompt referral to memory clinics in the United Kingdom: Cluster randomised controlled trial - Livingston, Gill; Baio, Gianluca; Sommerlad, Andrew; de Lusignan, Simon; Poulimenos, Spyridon; Morris, Steve; Rait, Greta; Hoe, Juanita (PLoS medicine, 2017)
Most people with dementia do not receive timely diagnosis, preventing them from making informed plans about their future and accessing services. Many countries have a policy to increase timely diagnosis, but trials aimed at changing general practitioner (GP) practice have been unsuccessful. We aimed to assess whether a GP's personal letter, with an evidence-based leaflet about overcoming barriers to accessing help for memory problems-aimed at empowering patients and families-increases timely dementia diagnosis and patient presentation to general practice. Multicentre, cluster-randomised controlled trial with raters masked to an online computer-generated randomisation system assessing 1 y outcome. We recruited 22 general practices (August 2013-September 2014) and 13 corresponding secondary care memory services in London, Hertfordshire, and Essex, United Kingdom. Eligible patients were aged ≥70 y, without a known diagnosis of dementia, living in their own homes. There were 6,387 such patients in 11 intervention practices and 8,171 in the control practices. The primary outcome was cognitive severity on Mini Mental State Examination (MMSE). Main secondary outcomes were proportion of patients consulting their GP with suspected memory disorders and proportion of those referred to memory clinics. There was no between-group difference in cognitive severity at diagnosis (99 intervention, mean MMSE = 22.04, 95% confidence intervals (CIs) = 20.95 to 23.13; 124 control, mean MMSE = 22.59, 95% CI = 21.58 to 23.6; p = 0.48). GP consultations with patients with suspected memory disorders increased in intervention versus control group (odds ratio = 1.41; 95% CI = 1.28, 1.54). There was no between-group difference in the proportions of patients referred to memory clinics (166, 2.5%; 220, 2.7%; p = .077 respectively). The study was limited as we do not know whether the additional patients presenting to GPs had objective as well as subjective memory problems and therefore should have been referred. In addition, we aimed to empower patients but did not do anything to change GP practice. Our intervention to access timely dementia diagnosis resulted in more patients presenting to GPs with memory problems, but no diagnoses increase. We are uncertain as to the reason for this and do not know whether empowering the public and targeting GPs would have resulted in a successful intervention. Future interventions should be targeted at both patients and GPs. Current Controlled Trials ISRCTN19216873.